The esperanza window trap reduces the human biting rate of Simulium ochraceum s.l. in formerly onchocerciasis endemic foci in Southern Mexico. - Mario A Rodríguez-Pérez; Javier A Garza-Hernández; Mario C Salinas-Carmona; Ildefonso Fernández-Salas; Filiberto Reyes-Villanueva; Olga Real-Najarro; Eddie W Cupp; Thomas R Unnasch (Public Library of Science (PLoS), 2017)
The Esperanza Window Trap (EWT) baited with CO2 and human sweat compounds is attractive to Simulium ochraceum s.l., the primary vector of Onchocerca volvulus in the historically largest endemic foci in México and Guatemala.The ability of the EWT to locally reduce numbers of questing S. ochraceum s.l. was evaluated in two formerly onchocerciasis endemic communities in Southern México. At each community, two EWTs were placed in or near a school or household and flies were collected sequentially for a total of 10 days. Black fly collections were then carried out for an additional 10 days in the absence of the EWTs. Flies were also collected outside the dwellings to control for variations in the local fly populations. When the EWTs were present, there was a significant reduction in the human biting rate at both the household and school locations at collection sites, with a greater effect observed in the schools.These results indicate that the EWTs not only have potential as a black fly monitoring tool but may be used for reducing personal exposure to fly bites in Mesoamerica.